Lyciumbarbarum Polysaccharide (LBP): A Novel Prebiotics Candidate for Bifidobacterium and Lactobacillus - Zhou, Fang; Jiang, Xiaoying; Wang, Tao; Zhang, Bolin; Zhao, Hongfei (Frontiers in Microbiology, 2018)
Lycium barbarum is a boxthorn that produces the goji berries. The aim of the current study was to evaluate the proliferative effect of L. barbarum polysaccharides (LBP) on probiotics. LBP was extracted from goji berries and its monosaccharide composition characterized by gas chromatography (GC). The LBP extract contained arabinose, rhamnose, xylose, mannose, galactose, and glucose. LBP obviously promoted the proliferation of lactic acid bacteria (LAB) strains, especially Bifidobacterium longum subsp. infantis Bi-26 and Lactobacillus acidophilus NCFM. In the presence of LBP in the growth medium, the -galactosidase (-GAL) and lactate dehydrogenase (LDH) activities of strain Bi-26 significantly increased. The activities of -GAL, LDH, hexokinase (HK), 6-phosphofructokinase (PHK), and pyruvate kinase (PK) of strain NCFM significantly increased under those conditions. LAB transcriptome sequencing analysis was performed to elucidate the mechanism responsible for the proliferative effect of LBP. The data revealed that LBP promoted the bacterial biosynthetic and metabolic processes, gene expression, transcription, and transmembrane transport. Pyruvate metabolism, carbon metabolism, phosphotransferase system (PTS), and glycolysis/gluconeogenesis genes were overexpressed. Furthermore, LBP improved cell vitality during freeze-drying and tolerance of the gastrointestinal environment. In summary, LBP can be used as a potential prebiotic for Bifidobacterium and Lactobacillus.